2020
DOI: 10.3389/fphar.2019.01528
|View full text |Cite
|
Sign up to set email alerts
|

Dihydrotestosterone Regulates Hair Growth Through the Wnt/β-Catenin Pathway in C57BL/6 Mice and In Vitro Organ Culture

Abstract: Dihydrotestosterone (DHT) is the most potent androgen that regulates hair cycling. Hair cycling involves cross-talk between the androgen and Wnt/b-catenin pathways. However, how DHT regulates hair follicle (HF) growth through the Wnt/b-catenin pathway has not been well investigated. This study aimed to investigate the roles of DHT in hair growth in vivo and in vitro. Human scalp HFs were treated with different concentrations of DHT (10-5 , 10-6 , 10-7 , 10-8 , and 10-9 mol/L) for 10 days. The effects of DHT on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…In this study, after topical application of testosterone propionate solution, the dorsal hair growth by C57BL/6 mice was inhibited by disturbing the synchronized growth cycle at the initial stage [40]. Changes in the hair growth cycle resulted in skin color changes from fleshy pink to gray and black, as previously described [30,41]. In the present study, after C57BL/6 mice had ingested PL, hair growth in dorsal skin was quickly started, and the numbers and sizes of hair follicles increased, suggesting that hair quickly entered the growth phase.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In this study, after topical application of testosterone propionate solution, the dorsal hair growth by C57BL/6 mice was inhibited by disturbing the synchronized growth cycle at the initial stage [40]. Changes in the hair growth cycle resulted in skin color changes from fleshy pink to gray and black, as previously described [30,41]. In the present study, after C57BL/6 mice had ingested PL, hair growth in dorsal skin was quickly started, and the numbers and sizes of hair follicles increased, suggesting that hair quickly entered the growth phase.…”
Section: Discussionsupporting
confidence: 55%
“…The potentiation of Akt and GSK-3β phosphorylation improved Wnt signaling to protect against hair loss induced by testosterone. Finasteride provides a recognized treatment for AGA [6,41,45] and has also been used to treat prostate cancer [46]. We demonstrated that finasteride had no apparent effect on hair growth during the early stage of the experiment, but that subsequently, it quickly promoted hair growth.…”
Section: Discussionmentioning
confidence: 78%
“…The relative expression levels of β -catenin, Wnt3a, and Wnt10b were analyzed by the Image Pro-Plus 6.0 software. Briefly, images were converted into a black and white mode at first; then, the integrated optical density (IOD) and the area of the positive region (AREA) were calculated; finally, the mean density is obtained as IOD/AREA to indicate the relative expression levels [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, apart from the mentioned involvements in various physiological conditions, dysregulation of Wnt/β-catenin signaling is strongly associated with the development of AGA—a dermatological disorder whereby the hair is abnormally shed from the skin where it normally should be presented. Particularly, it is suppressed in AGA [ 13 , 22 , 24 , 25 , 26 , 27 ]. Indeed, various Wnt proteins play a substantial role in the hair growth cycle [ 2 ].…”
Section: The Importance Of Wnt/β-catenin Signaling In Hair Growthmentioning
confidence: 99%